SHARE PRICE ANALYSIS OF PT HEXINDO ADIPERKASA, TBK AT THE TIME DATE AND EX DATE - Vargo Christian L. Tobing; Eva Malina Simatupang (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2023)
Shares are proof that investors have an interest in the company. The company's stock price always fluctuates. Many factors cause the stock price of a company to fluctuate. In this study, the company used as the object of research was PT Hexindo Adiperkasa, Tbk. The data used as research material was data on the company's stock price in September, which was 1 week before the date and 1 week after the ex date. Because September is the time when the opportunity for potential investors or investors to own shares of issuers in order to get profits in the form of dividends. From the results of the study, it can be seen that the share price of issuers before the date has increased, because many potential investors or investors have made requests to buy shares. However, during the ex date and a few days after the ex date, the company's stock price declined. This is because many investors make offers or sales of shares. The number of investors who make offers or sells shares is more than the demand for buying shares, conditions like this cause a decrease in stock prices